2001
DOI: 10.2307/1592896
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Characterization of a Pigeon Paramyxovirus Type-1 Isolate Found in Argentina

Abstract: In this report, we describe the biological and molecular characterization of a paramyxovirus type-1 (PPMV-1) isolate found in wild pigeons in an urban habitat in Buenos Aires, Argentina. Of the nine pigeons captured, three were moribund, and the other six showed diarrhea, ataxia, tremor, torticolis, and wing paralysis. The intracerebral pathogenicity index was 1.29, and the amino acid (aa) sequence at the fusion protein cleavage site was 112GRQ KRF117. These characteristics correspond to a virulent Newcastle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
4
14
0
Order By: Relevance
“…Several outbreaks in Columbiformes have been reported over the past 30 years in many parts of the world caused by an adapted variant AAvV-1 denominated pigeon paramyxovirus 1 (PPMV-1) (Alexander 2011), which have been described in countries of the South America (Zanetti et al 2001). These panzootic strains belong to genotype VI, which presents 9 subgenotypes (Dimitrov et al 2016), and has been previously described in high mortality outbreaks worldwide in different species of birds (Alexander et al 1985(Alexander et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Several outbreaks in Columbiformes have been reported over the past 30 years in many parts of the world caused by an adapted variant AAvV-1 denominated pigeon paramyxovirus 1 (PPMV-1) (Alexander 2011), which have been described in countries of the South America (Zanetti et al 2001). These panzootic strains belong to genotype VI, which presents 9 subgenotypes (Dimitrov et al 2016), and has been previously described in high mortality outbreaks worldwide in different species of birds (Alexander et al 1985(Alexander et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Avian paramyxoviruses, including Newcastle disease virus, are common domestic and wild bird pathogens [27][28][29][30]. Paramyxovirus type-1 can be found in pigeons worldwide [31][32][33][34] but the clinical signs vary depending on the immunity of the host and virulence of the specific isolates [35]. While human infection with Newcastle disease virus is rare, at least two outbreaks of conjunctivitis due to Newcastle disease virus have been reported in poultry workers [28,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, in 1984, multiple ND outbreaks in Great Britain were initiated by PPMV1 and spread from pigeons to chickens (Alexander et al, 1985b). Subsequently, PPMV1 has been responsible for other chicken ND outbreaks worldwide (Aldous et al, 2004;Capua et al, 2002;Kommers et al, 2001;Liu et al, 2006;OIE, 2011a,b;Toro et al, 2005;Werner et al, 1999) and has caused extensive panzootic infections in racing pigeons in European countries despite vaccination efforts (Alexander et al, 1997;Kommers et al, 2001;Meulemans et al, 2002;Werner et al, 1999;Zanetti et al, 2001). Genetic analysis of PPMV1 demonstrated that this strain, named genotype VI-PMV1 (GVI-PMV1) (Aldous et al, 2004), constituted a distinct monophyletic lineage with considerable genetic heterogeneity.…”
Section: Introductionmentioning
confidence: 99%